Frequent Flyers: Stressors and Coping Strategies - Pitkänen, Pia Johanna (My University, 2012)
The first aim of this study is to bring out, what kind of challenges, issues and concerns that can cause stress, frequent flyers confront in their life, where the travelling aspect is playing a big part. The lifestyle of these frequent flyers can be very hectic and without permanent routines. Stress causing occasions and issues are quite easy to find out and for that, the main aim of this study is to fill the gap concerning the coping strategies of internationally working mobile employees, and bring out, how they cope with all the demands, situations, and expectations that they have. Coping cannot be studied without profound investigation of stress, and for that reason it was crucial to make clear, what kind of things cause stress before, during, and after international business trips. 10 frequent flyers were interviewed within October and November 2011. All the interviews were conducted in Finnish and later on translated into English, to fit in this study. The duration of the interviews varied between app. 30-60 minutes and they were recorded. All the 10 interviews were conducted by the researcher of this study and were also transcribed by the researcher herself to enable closer examination after all the interviews were performed. Two out of ten respondents were women and eight of ten were men. Age varied between 28-55 years and only two of the respondents were single and childless. Duration of employment (within the same company) vary from 4 to 26 years. Every respondent works as a manager in some level within the organization. Former literature and the conducted 10 interviews showed that frequent flyers have many things to stress about and it can be seen that the most stressful stage according to the interviews is the pre-trip stage for the travelers because of the preparation, packing and scheduling, but the biggest amount of different types of stressful situations can be found from on-trip stage. Pre-trip stressors are quite certain. Every time the traveler has to be prepared for the trip and if the announcement of the trip comes sudden, there is no time for proper preparation and that causes stress. During the trip the stressful situations are often sudden and come as a surprise such as cancellations and delays. There could not be found many stressful situations from the post-trip stage but piled up work load was mentioned. The reason for some FFs can be that it is impossible for work during the trip and it causes that the work load is bigger when returning back to the home office. The coping strategies that FFs use can be problem focused or emotional focused forms of coping and the strategies can take place before (proactive), during or after (reactive) the stressful situation. It seems that the frequent flyers use both emotional, and problem focused coping strategies with wide range of both. Frequent flyers are often part of the companies´ management and they often are skilled to solve problems and deal with different kind of situations. It seems that these travelers want to be on the top of the situations and control things as far as possible. Concluding from the interviews they pursue to use active tendencies as much as possible to cope with stressful situations as well as possible and when the problem solving manners are used and they interpret that there are nothing more to do about the challenging, stressful situation, the emotional focused coping strategies takes place.
Keywords: Frequent Flyer; Short-Time Assignment; Stress; Coping Strategies; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master's Degree Programme in International Business|